CUSTOMIZED FINISHING TECHNIQUES ON ENTRY LEVEL FDM 3D PRINTED ARTEFACTS IN VISUAL ARTS: An explanatory sequential study. - Sarel, Pretorius, Havenga (Bloemfontein: Central University of Technology, Free State, 2017)
The aim of this study is to investigate ways to improve the quality of entry-level fused deposition modelling (ELFDM) produced artefacts, to make the technology more accessible to a wider range of prosumer and address the scale limitations of production components. The development of entry-level 3D printed (EL3DP) technology enhances art and design by providing new techniques previously impossible; however limitations such as poor surface finish quality and size limitations are persistently observed. These limitations steer artists and designers away from utilizing this technology due to poor aesthetic value outputs. It was necessary to construct this study from within an explanatory sequential mixed method paradigm as both quantitative and qualitative data were needed to sketch a broad overview and analyse abstract concepts like aesthetic value. Due to the lack of recorded academic information an experimental pilot study was first conducted to identify potential techniques, followed by quantitative (tensile tests and surface profile measurements) and qualitative (in depth interviews and online surveys) phases and lastly all the data was interpreted to cohesively substantiate the hypothesis. The results show that the pre-experimental pilot study identified potential techniques that were investigated in the phases that followed. Clear evidence is shown to support the progression of ELFDM technique development by applying post-production finishing techniques (PPFTs). It also indicates that the aesthetic value of an artefact can be enhanced by applying surface finishing and assembly techniques. This study enables a larger range of entry-level prosumer to utilize cheaper alternatives to Additive Manufacturing (AM) technologies which will lessen the gap between high-end and entry-level. Furthermore by affecting the strength and surface texture of ELFDM 3D prints it has a direct influence on the aesthetic value and functionality of EL3DP artefacts.
Published Thesis
Keywords: Acetone; Acrylonitrile Butadiene Styrene; Artefacts; Fused Deposition Modelling; Post-production; Post-processing; Surface finish; Tensile strength; Post-production finishing techniques